Post-treatment Method for the Synthesis of Monodisperse Binary FePt-Fe3O4 Nanoparticles - Zhilu Liu (Nanoscale Research Letters, 2017)
Abstract To obtain the optimal 1:1 composition of FePt alloy nanomaterials by polyol synthesis, the iron precursor (iron pentacarbonyl, Fe(CO)5) must be used in excess, because the Fe(CO)5 exists in the vapor phase at the typical temperatures used for FePt synthesis and cannot be consumed completely. Fabrication of Fe3O4 nanoparticles by consuming the excess iron precursor was an effective strategy to make full use of the iron precursor. In this paper, a facile post-treatment method was applied to consume the excess iron, which was oxidized to Fe3O4 after post-treatment at 150 and 200 °C, and a monodisperse binary FePt-Fe3O4 nanoparticle system was generated. The post-treatment method did not affect the crystal structure, grain size, or composition of the FePt nanoparticles. However, the content and grain size of the fcc-Fe3O4 nanoparticles can be increased simply by increasing the post-treatment temperature from 150 to 200 °C.